Sosialisasi Pencegahan Narkoba, Kamseltibcar Lantas dan Human Trafficking : di wilayah Hukum Polda Lampung - Ilham Prisgunanto (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Crime is so real in everyday life. In fact, crime can be prevented if humans understand that crime exists in their lives. The College of Police Science (STIK) is trying to take preventive action by providing socialization on several crimes such as drug abuse in adolescents, driving safety for citizens and human trafficking in the jurisdiction of the Lampung Regional Police. With a good understanding of the citizens will of course prevent the spread of the pattern of crime in question. This community service uses the methods of discussion, outreach, hospitality to Muspida officials, counseling, social services, community service, visits there and visits to the community. The result is that the community responds seriously and enthusiastically to the socialization of these crimes and gains a better understanding of the patterns of action and the possibility of dealing with these crimes in the future.